2017
DOI: 10.21608/ejrs.2017.41822
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Blood Constituents and Some Physiological Parameters of Rabbit Bucks Administered With Bee Pollen Under Hot Conditions Prevalent in Assiut

Abstract: The impact of treatment with bee pollen (BP) on the productive performance and some hematological and physiological traits of rabbit bucks were studied under hot climatic conditions prevalent in Assiut during the summer season. A number of 30 rabbit bucks (15 Vline & 15 Moshtohor line); 14 weeks old were divided into three equal experimental groups. The bucks of 1 st group were fed on a commercial basal ration and served as control, while those in the 2 nd and 3 rd groups were fed on the same ration in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Also, the PCV ratio in BP2 and DPP2 rabbits were highest (P<0.05) compared with the C group by (20.74% and 17.65%, respectively). The present study results indicated that treating rabbits with DPP and BP had improved the hematological variables, which are in agreement with the previous results of Abuoghaba et al, (2017), El-Neney and El-Kholy, (2014), Khalil et al, (2015), andTaghian, et al (2017). Treatment with both 250 and 500 mg BP/buck of rabbit bucks raised in hot, humid environments showed significant improvement in the RBCs, lymphocytes, and neutrophils parameters (Abuoghaba et al, 2017).…”
Section: Blood Cells Contentssupporting
confidence: 93%
See 2 more Smart Citations
“…Also, the PCV ratio in BP2 and DPP2 rabbits were highest (P<0.05) compared with the C group by (20.74% and 17.65%, respectively). The present study results indicated that treating rabbits with DPP and BP had improved the hematological variables, which are in agreement with the previous results of Abuoghaba et al, (2017), El-Neney and El-Kholy, (2014), Khalil et al, (2015), andTaghian, et al (2017). Treatment with both 250 and 500 mg BP/buck of rabbit bucks raised in hot, humid environments showed significant improvement in the RBCs, lymphocytes, and neutrophils parameters (Abuoghaba et al, 2017).…”
Section: Blood Cells Contentssupporting
confidence: 93%
“…The present study results indicated that treating rabbits with DPP and BP had improved the hematological variables, which are in agreement with the previous results of Abuoghaba et al, (2017), El-Neney and El-Kholy, (2014), Khalil et al, (2015), andTaghian, et al (2017). Treatment with both 250 and 500 mg BP/buck of rabbit bucks raised in hot, humid environments showed significant improvement in the RBCs, lymphocytes, and neutrophils parameters (Abuoghaba et al, 2017). Also, BP significantly increased RBC and WBC counts in rabbits compared with control (Neney and El-Kholy, 2014).…”
Section: Blood Cells Contentssupporting
confidence: 93%
See 1 more Smart Citation
“…Despite some of these substances being considered by-products, they are sources of bioactive compounds with relevant biological effects and significant impacts on animal physiological and productive performance [4,29,30]. Several studies have found that bee products, with a high content of essential amino acids, antioxidants, active enzymes, vitamins, minerals, antibacterial, antiprotozoal, and immunostimulant substances, can improve animals' growth, meat quality, and immunological performance [3,4,[31][32][33][34] (Figure 1). Rabie et al [29] found that administering propolis (400 mg/kg diet) or bee-pollen (2 g/kg diet) to the broiler diets as well as adding bee-venom (2 mg/L water) to broiler drinking water is recommended instead of using antibiotics in broiler farms to increase body weight and improve blood biochemical indices.…”
Section: Propolismentioning
confidence: 99%
“…According to Yıldız et al [77], supplementation of bee pollen under stress lowered the oxidative stress indicators and increased the antioxidant system of animals. Moreover, Abuoghaba et al [31] found that dietary supplementation of bee pollen (500 and 1000 mg/kg diet) to breeder hens improved several hatching and hematological traits, in addition to reducing the adverse effects of heat stress on chicks treated with thermal manipulation during egg incubation.…”
Section: Bee Pollenmentioning
confidence: 99%